Pemanfaatan Ekosistem Mangrove bagi Minimasi Dampak Bencana di Wilayah Pesisir - Emi Karminarsih (Institut Pertanian Bogor (IPB University), 2007)
Indonesian beach region laid down in the critical area on nature disaster like tsunami. Tsunami on December 26, 2004, has greatly destroyed beach region in several districts in NAD and Nias. This disaster had raised responses from Indonesian people, especially on attempt to reserve the beach area to decrease the damaged of tsunami. One effort on rehabilitation the damaged beach area were through planting mangrove. Mangrove forest ecosystem are a unique beach ecosystem about form of steam, canopy and root system. Growth the best on muddy beach with influenced by the high and low tide and salty water. This vegetations have many important as a nature reserve beach area especially to minimized the disaster of tsunami. Besides this, the area and distribution of ecosystem mangrove has decrease by continue until now. Tsunami on December 26, 2004 has bring the nations of Indonesia more be awared on the important to protect and conservation of mangrove forest. Government, private, and NGO, have the prioritas of savety beach area by planting mangrove.